2018
DOI: 10.1093/ecco-jcc/jjy213
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the Hyper-immune Bovine Colostrum Extract IMM-124E Ameliorates Experimental Murine Colitis

Abstract: Background/Aims Inflammatory bowel disease (IBD) is accompanied by lesions in the epithelial barrier, which allow translocation of bacterial products from the gut lumen to the host's circulation. IMM-124E is a colostrum-based product, containing high levels of anti-E.coli-LPS IgG and might limit exposure to bacterial endotoxins. Here, we investigated whether IMM-124E can ameliorate intestinal inflammation. Methods Acute colitis was induced in WT C57Bl/6J mice by administration of 2.5% DSS for 7 days. T cell tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…They obtained improvements of DAI and symptoms by using hyperimmune colostrum, on the other hand, the administration of raw BC did not show any significant amelioration on TNBS-induced colitis in mice. Conversely, other authors [8,24] have recently reported that also colostrum from nonimmunized cows can reduced BW losses, DAI and histological score in DSS-induced murine models of IBD. In humans, the administration of BC by enema for 4 weeks improved the clinical and histological score in patients affected by active colitis compared to control [7].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…They obtained improvements of DAI and symptoms by using hyperimmune colostrum, on the other hand, the administration of raw BC did not show any significant amelioration on TNBS-induced colitis in mice. Conversely, other authors [8,24] have recently reported that also colostrum from nonimmunized cows can reduced BW losses, DAI and histological score in DSS-induced murine models of IBD. In humans, the administration of BC by enema for 4 weeks improved the clinical and histological score in patients affected by active colitis compared to control [7].…”
Section: Discussionmentioning
confidence: 92%
“…Currently, the precise mechanisms involved in the pathogenesis of IBD are largely unknown, and a perfect model for their investigation does not exist. For these reasons, in recent years, many animal models and various chemical compounds have been employed to study its pathogenesis [8,26,28]. In our study, we designed the experimental procedures using the haptenic agent TNBS, which induces the disruption of the intestinal barrier and elicits a significant immune response that resembles IBD in regard to clinical symptoms and histopathology [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations